The black phone [videorecording (DVD)] - Hawke, Ethan, 1970-; Davies, Jeremy, 1969-; Ransone, James, 1979-; McGraw, Madeleine, 2008-; Thames, Mason; Wilde, J. Gaven; Hepner, Brady; Moran, Jacob; Arjona, Kristina; Hill, Joe (Universal, 2022)
Finney Shaw is a shy but clever 13-year-old boy who's being held in a soundproof basement by a sadistic, masked killer. When a disconnected phone on the wall starts to ring, he soon discovers that he can hear the voices of the murderer's previous victims, and they are dead set on making sure that what happened to them doesn't happen to Finney.